ANALYZING THE INTERSECTION OF SMOKING CONSEQUENCES IN ISLAMIC JURISPRUDENCE AND ITS DIVERSE PERSPECTIVES - Muhammad Labib; Syahrullah; Raghib Filhaq; Fakhrurazi Reno Sutan; Saiful Bahri (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
The leading preventable cause of fatality in contemporary society is smoking. In Islamic law, smoking is inextricably linked to the examination of the Qur'an, Hadith, and Ijtihad. This literature review examines the intricate convergence of smoking repercussions and Islamic jurisprudence, delving into the varied viewpoints concerning this matter within the Islamic tradition. This research examines fundamental Islamic scriptures, such as the Al-Quran, Hadith, and Ijtihad, in order to reveal the diverse array of principles and perspectives that influence Islamic perspectives on smoking. A spectrum of perspectives exists within Islamic jurisprudence regarding smoking, ranging from permissibility to prohibition, according to a synthesis of the relevant literature. The research emphasizes the complex correlation between smoking and Islamic ethics, taking into account elements such as personal accountability and health repercussions. Furthermore, the analysis discerns significant themes and recurring arguments that influence the varied viewpoints on smoking in Islamic thought as presented in the literature. In summary, this literature review highlights the intricacy of the matter through its provision of an all-encompassing examination of the varied viewpoints concerning the repercussions of smoking within the realm of Islamic jurisprudence. The results of this research enhance our comprehension of the ethical implications and difficulties linked to smoking in an Islamic framework. As a result, policymakers, practitioners, and scholars in the disciplines of health and religious studies will gain invaluable knowledge from these results.